/- Copyright (c) 2016 Robert Y. Lewis. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Author: Robert Y. Lewis Bounded linear operators -/ import .normed_space .real_limit algebra.module algebra.homomorphism open real nat classical topology set --open normed_vector_space (this confuses lots of stuff??) noncomputable theory namespace analysis -- define bounded linear operators and basic instances section bdd_lin_op structure is_bdd_linear_map [class] {V W : Type} [normed_vector_space V] [normed_vector_space W] (f : V → W) extends is_module_hom ℝ f := (op_norm : ℝ) (op_norm_pos : op_norm > 0) (op_norm_bound : ∀ v : V, ∥f v∥ ≤ op_norm * ∥v∥) theorem is_bdd_linear_map_id [instance] (V : Type) [normed_vector_space V] : is_bdd_linear_map (λ x : V, x) := begin fapply is_bdd_linear_map.mk, repeat (intros; reflexivity), exact 1, exact zero_lt_one, intro, rewrite one_mul, apply le.refl end theorem is_bdd_linear_map_zero [instance] (V W : Type) [normed_vector_space V] [normed_vector_space W] : is_bdd_linear_map (λ x : V, (0 : W)) := begin fapply is_bdd_linear_map.mk, all_goals intros, rewrite zero_add, rewrite smul_zero, exact 1, exact zero_lt_one, rewrite [norm_zero, one_mul], apply norm_nonneg end theorem is_bdd_linear_map_add [instance] {V W : Type} [normed_vector_space V] [normed_vector_space W] (f g : V → W) [Hbf : is_bdd_linear_map f] [Hbg : is_bdd_linear_map g] : is_bdd_linear_map (λ x, f x + g x) := begin fapply is_bdd_linear_map.mk, all_goals intros, {rewrite [hom_add f, hom_add g],-- (this takes 4 seconds: rewrite [2 hom_add]) simp}, {rewrite [hom_smul f, hom_smul g, smul_left_distrib]}, {exact is_bdd_linear_map.op_norm _ _ f + is_bdd_linear_map.op_norm _ _ g}, {apply add_pos, repeat apply is_bdd_linear_map.op_norm_pos}, {apply le.trans, apply norm_triangle, rewrite right_distrib, apply add_le_add, repeat apply is_bdd_linear_map.op_norm_bound} end theorem is_bdd_linear_map_smul [instance] {V W : Type} [normed_vector_space V] [normed_vector_space W] (f : V → W) (c : ℝ) [Hbf : is_bdd_linear_map f] : is_bdd_linear_map (λ x, c • f x) := begin apply @decidable.cases_on (c = 0), exact _, {intro Hcz, rewrite Hcz, have Hfe : (λ x : V, (0 : ℝ) • f x) = (λ x : V, 0), from funext (λ x, !zero_smul), rewrite Hfe, apply is_bdd_linear_map_zero}, intro Hcnz, fapply is_bdd_linear_map.mk, all_goals intros, {rewrite [hom_add f, smul_left_distrib]}, {rewrite [hom_smul f, -*mul_smul, {c*r}mul.comm]}, {exact (abs c) * is_bdd_linear_map.op_norm _ _ f}, {have Hpos : abs c > 0, from abs_pos_of_ne_zero Hcnz, apply mul_pos, assumption, apply is_bdd_linear_map.op_norm_pos}, {rewrite [norm_smul, mul.assoc], apply mul_le_mul_of_nonneg_left, apply is_bdd_linear_map.op_norm_bound, apply abs_nonneg} end theorem is_bdd_linear_map_neg [instance] {V W : Type} [normed_vector_space V] [normed_vector_space W] (f : V → W) [Hbf : is_bdd_linear_map f] : is_bdd_linear_map (λ x, -f x) := begin have H : (λ x : V, -f x) = (λ x : V, (-1 : ℝ) • f x), from funext (λ x, eq.symm !neg_one_smul), rewrite H, apply is_bdd_linear_map_smul end -- this can't be an instance because things loop theorem is_bdd_linear_map_comp {U V W : Type} [normed_vector_space U] [normed_vector_space V] [normed_vector_space W] (f : V → W) (g : U → V) [is_bdd_linear_map f] [is_bdd_linear_map g] : is_bdd_linear_map (λ u, f (g u)) := begin fapply is_bdd_linear_map.mk, all_goals intros, {rewrite [hom_add g, hom_add f]}, {rewrite [hom_smul g, hom_smul f]}, {exact is_bdd_linear_map.op_norm _ _ f * is_bdd_linear_map.op_norm _ _ g}, {apply mul_pos, repeat apply is_bdd_linear_map.op_norm_pos}, {apply le.trans, apply is_bdd_linear_map.op_norm_bound _ _ f, apply le.trans, apply mul_le_mul_of_nonneg_left, apply is_bdd_linear_map.op_norm_bound _ _ g, apply le_of_lt !is_bdd_linear_map.op_norm_pos, rewrite *mul.assoc, apply le.refl} end variables {V W : Type} variables [HV : normed_vector_space V] [HW : normed_vector_space W] include HV HW variable f : V → W variable [Hf : is_bdd_linear_map f] include Hf definition op_norm := is_bdd_linear_map.op_norm _ _ f theorem op_norm_pos : op_norm f > 0 := is_bdd_linear_map.op_norm_pos _ _ f theorem op_norm_bound (v : V) : ∥f v∥ ≤ (op_norm f) * ∥v∥ := is_bdd_linear_map.op_norm_bound _ _ f v theorem bdd_linear_map_continuous : continuous f := begin apply continuous_of_forall_continuous_at, intro x, apply normed_vector_space.continuous_at_intro, intro ε Hε, existsi ε / (op_norm f), split, apply div_pos_of_pos_of_pos Hε !op_norm_pos, intro x' Hx', rewrite [-hom_sub f], apply lt_of_le_of_lt, apply op_norm_bound f, rewrite [-@mul_div_cancel' _ _ ε (op_norm f) (ne_of_gt !op_norm_pos)], apply mul_lt_mul_of_pos_left, exact Hx', apply op_norm_pos end end bdd_lin_op -- define Frechet derivative and basic properties section frechet_deriv variables {V W : Type} variables [HV : normed_vector_space V] [HW : normed_vector_space W] include HV HW definition has_frechet_deriv_at (f A : V → W) [is_bdd_linear_map A] (x : V) := (λ h : V, ∥f (x + h) - f x - A h ∥ / ∥ h ∥) ⟶ 0 [at 0] lemma diff_quot_cts {f A : V → W} [HA : is_bdd_linear_map A] {y : V} (Hf : has_frechet_deriv_at f A y) : continuous_at (λ h, ∥f (y + h) - f y - A h∥ / ∥h∥) 0 := begin apply normed_vector_space.continuous_at_intro, intro ε Hε, cases normed_vector_space.approaches_at_dest Hf Hε with δ Hδ, existsi δ, split, exact and.left Hδ, intro x' Hx', cases em (x' = 0) with Heq Hneq, {rewrite [Heq, norm_zero, div_zero, sub_zero, norm_zero], apply Hε}, {rewrite [norm_zero, div_zero], apply and.right Hδ, repeat assumption} end theorem is_bdd_linear_map_of_eq {A B : V → W} [HA : is_bdd_linear_map A] (HAB : A = B) : is_bdd_linear_map B := begin fapply is_bdd_linear_map.mk, all_goals try rewrite -HAB, {apply hom_add}, {apply hom_smul}, {exact op_norm A}, {exact op_norm_pos A}, {rewrite -HAB, apply op_norm_bound} end definition is_frechet_deriv_at_of_eq {f A : V → W} [is_bdd_linear_map A] {x : V} (Hfd : has_frechet_deriv_at f A x) {B : V → W} (HAB : A = B) : @has_frechet_deriv_at _ _ _ _ f B (is_bdd_linear_map_of_eq HAB) x := begin unfold has_frechet_deriv_at, rewrite -HAB, apply Hfd end theorem has_frechet_deriv_at_intro {f A : V → W} [is_bdd_linear_map A] {x : V} (H : ∀ ⦃ε : ℝ⦄, ε > 0 → (∃ δ : ℝ, δ > 0 ∧ ∀ ⦃x' : V⦄, x' ≠ 0 ∧ ∥x'∥ < δ → ∥f (x + x') - f x - A x'∥ / ∥x'∥ < ε)) : has_frechet_deriv_at f A x := begin apply normed_vector_space.approaches_at_intro, intros ε Hε, cases H Hε with δ Hδ, cases Hδ with Hδ Hδ', existsi δ, split, assumption, intros x' Hx'1 Hx'2, show abs (∥f (x + x') - f x - A x'∥ / ∥x'∥ - 0) < ε, begin have H : ∥f (x + x') - f x - A x'∥ / ∥x'∥ ≥ 0, from div_nonneg_of_nonneg_of_nonneg !norm_nonneg !norm_nonneg, rewrite [sub_zero, abs_of_nonneg H], apply Hδ', split, assumption, rewrite [-sub_zero x'], apply Hx'1 end end theorem has_frechet_deriv_at_elim {f A : V → W} [is_bdd_linear_map A] {x : V} (H : has_frechet_deriv_at f A x) : ∀ ⦃ε : ℝ⦄, ε > 0 → (∃ δ : ℝ, δ > 0 ∧ ∀ ⦃x' : V⦄, x' ≠ 0 ∧ ∥x'∥ < δ → ∥f (x + x') - f x - A x'∥ / ∥x'∥ < ε) := begin intros ε Hε, cases normed_vector_space.approaches_at_dest H Hε with δ Hδ, cases Hδ with Hδ Hδ', existsi δ, split, assumption, intros x' Hx', rewrite [-sub_zero x' at Hx' {2}], have Hδ'' : abs (∥f (x + x') - f x - A x'∥ / ∥x'∥ - 0) < ε, from Hδ' (and.right Hx') (and.left Hx'), have Hpos : ∥f (x + x') - f x - A x'∥ / ∥x'∥ ≥ 0, from div_nonneg_of_nonneg_of_nonneg !norm_nonneg !norm_nonneg, rewrite [sub_zero at Hδ'', abs_of_nonneg Hpos at Hδ''], assumption end structure frechet_diffable_at [class] (f : V → W) (x : V) := (A : V → W) [HA : is_bdd_linear_map A] (is_fr_der : has_frechet_deriv_at f A x) variables f g : V → W variable x : V definition frechet_deriv_at [Hf : frechet_diffable_at f x] : V → W := frechet_diffable_at.A _ _ f x definition frechet_deriv_at_is_bdd_linear_map [instance] (f : V → W) (x : V) [Hf : frechet_diffable_at f x] : is_bdd_linear_map (frechet_deriv_at f x) := frechet_diffable_at.HA _ _ f x theorem frechet_deriv_spec [Hf : frechet_diffable_at f x] : (λ h : V, ∥f (x + h) - f x - (frechet_deriv_at f x h) ∥ / ∥ h ∥) ⟶ 0 [at 0] := frechet_diffable_at.is_fr_der _ _ f x theorem has_frechet_deriv_at_const (w : W) : has_frechet_deriv_at (λ v : V, w) (λ v : V, 0) x := begin apply normed_vector_space.approaches_at_intro, intros ε Hε, existsi 1, split, exact zero_lt_one, intros x' Hx' _, rewrite [2 sub_self, norm_zero], krewrite [zero_div, sub_zero, norm_zero], assumption end theorem has_frechet_deriv_at_id : has_frechet_deriv_at (λ v : V, v) (λ v : V, v) x := begin apply normed_vector_space.approaches_at_intro, intros ε Hε, existsi 1, split, exact zero_lt_one, intros x' Hx' _, have x + x' - x - x' = 0, by simp, rewrite [this, norm_zero, zero_div, sub_self, norm_zero], exact Hε end theorem has_frechet_deriv_at_smul (c : ℝ) {A : V → W} [is_bdd_linear_map A] (Hf : has_frechet_deriv_at f A x) : has_frechet_deriv_at (λ y, c • f y) (λ y, c • A y) x := begin eapply @decidable.cases_on (abs c = 0), exact _, {intro Hc, have Hz : c = 0, from eq_zero_of_abs_eq_zero Hc, have Hfz : (λ y : V, (0 : ℝ) • f y) = (λ y : V, 0), from funext (λ y, !zero_smul), --have Hfz' : (λ x : V, (0 : ℝ) • A x) = (λ x : V, 0), from funext (λ y, !zero_smul), -- rewriting Hfz' produces type-incorrect term rewrite [Hz, Hfz], apply metric_space.approaches_at_intro, intro ε Hε, existsi 1, split, exact zero_lt_one, intro x' Hx' _, rewrite [zero_smul, *sub_zero, norm_zero], krewrite [zero_div, dist_self], exact Hε}, intro Hcnz, apply normed_vector_space.approaches_at_intro, intros ε Hε, have Hεc : ε / abs c > 0, from div_pos_of_pos_of_pos Hε (lt_of_le_of_ne !abs_nonneg (ne.symm Hcnz)), cases normed_vector_space.approaches_at_dest Hf Hεc with δ Hδ, cases Hδ with Hδp Hδ, existsi δ, split, assumption, intro x' Hx' _, show abs ((∥c • f (x + x') - c • f x - c • A x'∥ / ∥x'∥ - 0)) < ε, begin rewrite [sub_zero, -2 smul_sub_left_distrib, norm_smul], krewrite mul_div_assoc, rewrite [abs_mul, abs_abs, -{ε}mul_div_cancel' Hcnz], apply mul_lt_mul_of_pos_left, have Hδ' : abs (∥f (x + x') - f x - A x'∥ / ∥x'∥ - 0) < ε / abs c, from Hδ Hx' a, rewrite sub_zero at Hδ', apply Hδ', apply lt_of_le_of_ne, apply abs_nonneg, apply ne.symm, apply Hcnz end end theorem has_frechet_deriv_at_neg {A : V → W} [is_bdd_linear_map A] (Hf : has_frechet_deriv_at f A x) : has_frechet_deriv_at (λ y, - f y) (λ y, - A y) x := begin apply has_frechet_deriv_at_intro, intros ε Hε, cases has_frechet_deriv_at_elim Hf Hε with δ Hδ, existsi δ, split, exact and.left Hδ, intro x' Hx', rewrite [-norm_neg, neg_sub, sub_neg_eq_add, sub_add_eq_sub_sub, sub_neg_eq_add, add_sub_assoc, add.comm, -sub_eq_add_neg], apply and.right Hδ, assumption end theorem has_frechet_deriv_at_add (A B : V → W) [is_bdd_linear_map A] [is_bdd_linear_map B] (Hf : has_frechet_deriv_at f A x) (Hg : has_frechet_deriv_at g B x) : has_frechet_deriv_at (λ y, f y + g y) (λ y, A y + B y) x := begin have Hle : ∀ h, ∥f (x + h) + g (x + h) - (f x + g x) - (A h + B h)∥ / ∥h∥ ≤ ∥f (x + h) - f x - A h∥ / ∥h∥ + ∥g (x + h) - g x - B h∥ / ∥h∥, begin intro h, cases em (∥h∥ > 0) with Hh Hh, krewrite div_add_div_same, apply div_le_div_of_le_of_pos, have Hfeq : f (x + h) + g (x + h) - (f x + g x) - (A h + B h) = (f (x + h) - f x - A h) + (g (x + h) - g x - B h), by simp, rewrite Hfeq, apply norm_triangle, exact Hh, have Hhe : ∥h∥ = 0, from eq_of_le_of_ge (le_of_not_gt Hh) !norm_nonneg, krewrite [Hhe, *div_zero, zero_add], eapply le.refl end, have Hlimge : (λ h, ∥f (x + h) - f x - A h∥ / ∥h∥ + ∥g (x + h) - g x - B h∥ / ∥h∥) ⟶ 0 [at 0], begin rewrite [-zero_add 0], apply add_approaches, apply Hf, apply Hg end, have Hlimle : (λ (h : V), (0 : ℝ)) ⟶ 0 [at 0], by apply approaches_constant, apply approaches_squeeze Hlimle Hlimge, apply filter.eventually_of_forall, intro y, apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg, apply filter.eventually_of_forall, apply Hle end open topology theorem continuous_at_of_diffable_at [Hf : frechet_diffable_at f x] : continuous_at f x := begin apply normed_vector_space.continuous_at_intro, intros ε Hε, note Hfds := normed_vector_space.approaches_at_dest (frechet_deriv_spec f x) Hε, cases Hfds with δ Hδ, cases Hδ with Hδ Hδ', existsi min δ ((ε / 2) / (ε + op_norm (frechet_deriv_at f x))), split, {apply lt_min, exact Hδ, repeat apply div_pos_of_pos_of_pos, exact Hε, apply two_pos, apply add_pos Hε !op_norm_pos}, {intro x' Hx', cases em (x' - x = 0) with Heq Hneq, rewrite [eq_of_sub_eq_zero Heq, sub_self, norm_zero], assumption, have Hx'x : x' - x ≠ 0 ∧ ∥(x' - x) - 0∥ < δ, from and.intro Hneq begin rewrite sub_zero, apply lt_of_lt_of_le, apply Hx', apply min_le_left end, have Hx'xp : ∥x' - x∥ > 0, from norm_pos_of_ne_zero Hneq, have Hδ'' : abs (∥f (x + (x' - x)) - f x - frechet_deriv_at f x (x' - x)∥ / ∥x' - x∥ - 0) < ε, from Hδ' (and.right Hx'x) (and.left Hx'x), have Hnn : ∥f (x + (x' - x)) - f x - frechet_deriv_at f x (x' - x)∥ / ∥x' - x∥ ≥ 0, from div_nonneg_of_nonneg_of_nonneg !norm_nonneg !norm_nonneg, rewrite [sub_zero at Hδ'', abs_of_nonneg Hnn at Hδ'', add.comm at Hδ'', sub_add_cancel at Hδ''], note H1 := lt_mul_of_div_lt_of_pos Hx'xp Hδ'', have H2 : f x' - f x = f x' - f x - frechet_deriv_at f x (x' - x) + frechet_deriv_at f x (x' - x), by rewrite sub_add_cancel, --by simp, (simp takes .5 seconds to do this!) rewrite H2, apply lt_of_le_of_lt, apply norm_triangle, apply lt.trans, apply add_lt_add_of_lt_of_le, apply H1, apply op_norm_bound (!frechet_deriv_at), rewrite [-add_halves ε at {2}], apply add_lt_add, let on := op_norm (frechet_deriv_at f x), exact calc ε * ∥x' - x∥ < ε * min δ ((ε / 2) / (ε + on)) : mul_lt_mul_of_pos_left Hx' Hε ... ≤ ε * ((ε / 2) / (ε + on)) : mul_le_mul_of_nonneg_left !min_le_right (le_of_lt Hε) ... < ε / 2 : mul_div_self_add_lt (div_pos_of_pos_of_pos Hε two_pos) Hε !op_norm_pos, exact calc on * ∥x' - x∥ < on * min δ ((ε / 2) / (ε + on)) : mul_lt_mul_of_pos_left Hx' !op_norm_pos ... ≤ on * ((ε / 2) / (ε + on)) : mul_le_mul_of_nonneg_left !min_le_right (le_of_lt !op_norm_pos) ... < ε / 2 : mul_div_add_self_lt (div_pos_of_pos_of_pos Hε two_pos) Hε !op_norm_pos} end theorem continuous_at_of_has_frechet_deriv_at {A : V → W} [is_bdd_linear_map A] (H : has_frechet_deriv_at f A x) : continuous_at f x := begin apply @continuous_at_of_diffable_at, existsi A, exact H end end frechet_deriv section comp lemma div_mul_div_cancel {A : Type} [field A] (a b : A) {c : A} (Hc : c ≠ 0) : (a / c) * (c / b) = a / b := by rewrite [-mul_div_assoc, div_mul_cancel _ Hc] lemma div_add_eq_add_mul_div {A : Type} [field A] (a b c : A) (Hb : b ≠ 0) : (a / b) + c = (a + c * b) / b := by rewrite [-div_add_div_same, mul_div_cancel _ Hb] -- I'm not sure why smul_approaches doesn't unify where I use this? private lemma real_limit_helper {U : Type} [normed_vector_space U] {f : U → ℝ} {a : ℝ} {x : U} (Hf : f ⟶ a [at x]) (c : ℝ) : (λ y, c * f y) ⟶ c * a [at x] := begin apply smul_approaches, exact Hf end variables {U V W : Type} variables [HU : normed_vector_space U] [HV : normed_vector_space V] [HW : normed_vector_space W] variables {f : V → W} {g : U → V} variables {A : V → W} {B : U → V} variables [HA : is_bdd_linear_map A] [HB : is_bdd_linear_map B] variable {x : U} include HU HV HW HA HB -- this takes 2 seconds without clearing the contexts before simp theorem has_frechet_deriv_at_comp (Hg : has_frechet_deriv_at g B x) (Hf : has_frechet_deriv_at f A (g x)) : @has_frechet_deriv_at _ _ _ _ (λ y, f (g y)) (λ y, A (B y)) !is_bdd_linear_map_comp x := begin unfold has_frechet_deriv_at, note Hf' := has_frechet_deriv_at_elim Hf, note Hg' := has_frechet_deriv_at_elim Hg, have H : ∀ h, f (g (x + h)) - f (g x) - A (B h) = (A (g (x + h) - g x - B h)) + (-f (g x) + f (g (x + h)) + A (g x - g (x + h))), begin intro; rewrite [3 hom_sub A], clear [Hf, Hg, Hf', Hg'], simp end, -- .5 seconds for simp have H' : (λ h, ∥f (g (x + h)) - f (g x) - A (B h)∥ / ∥h∥) = (λ h, ∥(A (g (x + h) - g x - B h)) + (-f (g x) + f (g (x + h)) + A (g x - g (x + h)))∥ / ∥h∥), from funext (λ h, by rewrite H), rewrite H', clear [H, H'], apply approaches_squeeze, -- show the limit holds by bounding it by something that vanishes {apply approaches_constant}, rotate 1, {apply filter.eventually_of_forall, intro, apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg}, {apply filter.eventually_of_forall, intro, apply div_le_div_of_le_of_nonneg, apply norm_triangle, apply norm_nonneg}, have H : (λ (y : U), (∥A (g (x + y) - g x - B y)∥ + ∥-f (g x) + f (g (x + y)) + A (g x - g (x + y))∥) / ∥y∥) = (λ (y : U), (∥A (g (x + y) - g x - B y)∥ / ∥y∥ + ∥-f (g x) + f (g (x + y)) + A (g x - g (x + y))∥ / ∥y∥)), from funext (λ y, by rewrite [div_add_div_same]), rewrite [H, -zero_add 0], -- the function is a sum of two things that both vanish clear H, apply add_approaches, {apply approaches_squeeze, -- show the lhs vanishes by squeezing it again {apply approaches_constant}, rotate 1, {apply filter.eventually_of_forall, intro, apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg}, {apply filter.eventually_of_forall, intro y, show ∥A (g (x + y) - g x - B y)∥ / ∥y∥ ≤ op_norm A * (∥(g (x + y) - g x - B y)∥ / ∥y∥), begin rewrite -mul_div_assoc, apply div_le_div_of_le_of_nonneg, apply op_norm_bound A, apply norm_nonneg end}, {rewrite [-mul_zero (op_norm A)], apply real_limit_helper, apply Hg}}, -- we have shown the lhs vanishes. now the rhs {have H : ∀ y, (∥-f (g x) + f (g (x + y)) + A (g x - g (x + y))∥ / ∥y∥) = ((∥(f (g (x + y)) - f (g x)) - A (g (x + y) - g x) ∥ / ∥g (x + y) - g x∥) * (∥g (x + y) - g x∥ / ∥y∥)), begin intro, cases em (g (x + y) - g x = 0) with Heq Hneq, {note Heq' := eq_of_sub_eq_zero Heq, rewrite [Heq', neg_add_eq_sub, *sub_self, hom_zero A, add_zero, *norm_zero, div_zero, zero_div]}, {rewrite [div_mul_div_cancel _ _ (norm_ne_zero_of_ne_zero Hneq), *sub_eq_add_neg, -hom_neg A], clear [Hf, Hg, Hf', Hg', Hneq], simp} --(.5 seconds) end, apply approaches_squeeze, -- again, by squeezing {apply approaches_constant}, rotate 1, {apply filter.eventually_of_forall, intro, apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg}, {apply filter.eventually_of_forall, intro y, rewrite H, apply mul_le_mul_of_nonneg_left, {show ∥g (x + y) - g x∥ / ∥y∥ ≤ ∥g (x + y) - g x - B y∥ / ∥y∥ + op_norm B, begin cases em (y = 0) with Heq Hneq, {rewrite [Heq, norm_zero, *div_zero, zero_add], apply le_of_lt, apply op_norm_pos}, rewrite [div_add_eq_add_mul_div _ _ _ (norm_ne_zero_of_ne_zero Hneq)], apply div_le_div_of_le_of_nonneg, apply le.trans, rotate 1, apply add_le_add_left, apply op_norm_bound, apply norm_nonneg, rewrite [-neg_add_cancel_right (g (x + y) - g x) (B y) at {1}, -sub_eq_add_neg], apply norm_triangle end}, {apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg}}, -- now to show the bounding function vanishes. it is a product of a vanishing function and a convergent one apply mul_approaches_zero_of_approaches_zero_of_approaches, {have H' : (λ (y : U), ∥f (g (x + y)) - f (g x) - A (g (x + y) - g x)∥ / ∥g (x + y) - g x∥) = (λ (y : U), ∥f (g x + (g (x + y) - g x)) - f (g x) - A (g (x + y) - g x)∥ / ∥g (x + y) - g x∥), from funext (λ y, by rewrite [add.comm (g x), sub_add_cancel]), -- first, show lhs vanishes rewrite H', have Hgcts : continuous_at (λ y, g (x + y) - g x) 0, begin apply normed_vector_space.continuous_at_intro, intro ε Hε, cases normed_vector_space.continuous_at_dest (continuous_at_of_has_frechet_deriv_at g x Hg) _ Hε with δ Hδ, existsi δ, split, exact and.left Hδ, intro x' Hx', rewrite [add_zero, sub_self], rewrite sub_zero, apply and.right Hδ, have (x + x') - x = x' - 0, begin clear [Hg, Hf, Hf', Hg', H, H', Hδ, Hx'], simp end, -- (.6 seconds w/o clear, .1 with) rewrite this, apply Hx' end, have Hfcts : continuous_at (λ (x' : V), ∥f (g x + x') - f (g x) - A x'∥ / ∥x'∥) (g (x + 0) - g x), begin rewrite [add_zero, sub_self], apply diff_quot_cts, exact Hf end, have Heqz : ∥f (g x + (g (x + 0) - g x)) - f (g x) - A (g (x + 0) - g x)∥ / ∥g (x + 0) - g x∥ = 0, by rewrite [*add_zero, sub_self, norm_zero, div_zero], apply @tendsto_comp _ _ _ (λ y, g (x + y) - g x), apply tendsto_inf_left, apply tendsto_at_of_continuous_at Hgcts, note Hfcts' := tendsto_at_of_continuous_at Hfcts, rewrite Heqz at Hfcts', exact Hfcts'}, -- finally, show rhs converges to op_norm B {apply add_approaches, apply Hg, apply approaches_constant}} end end comp end analysis